PENGARUH JENIS INDUSTRI, SPESIALISASI INDUSTRI AUDITOR, DAN OPINI AUDITOR PADA AUDIT DELAY - Dwi Primantara, I Made; Rasmini, Ni Ketut (E-Jurnal Akuntansi, 2015)
An audit delay is the interval of time from the date book cover the annual financial report up to a date stamped on the report independent auditor .An audit a delay occur because of constraints in the implementation of the audit and this is in accordance with SPAP number three. This research aims to understand the influence of such types of industry, specialization industry an auditor, and opinion an audit on an audit a delay. The data used in this research obtained from the reports on financial publikasian manufacturing companies and finance at bei in 2013. The total sample used as many as 146 manufacturing companies and financial is determined on the basis of sampling techniques purposive. Data analysis technique that is used is linear regression worship of idols .The analysis shows that industry specialization the auditors and audit opinion have a negative influence on an audit a delay, while type of industry it does not affect on an audit a delay.
Keywords: Audit delay; Type of Industri; Auditor Industry Specialization; Auditor Opinion